Legal positions of the ECHR and the Supreme Court on the issues of breach of insurance obligations - Zaitseva-Kalaur , Inna; Khanas , Dmytro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article examines the legal positions of the European Court of Human Rights (ECHR) and the case law of the Supreme Court (SC) in the field of insurance, in particular, breach of insurance obligations. It is established that although the peculiarities of the development of insurance obligations have been studied in many aspects, scholars have not paid due interest and attention to the issues of studying and analysing the legal positions of the ECtHR and the SC on the issues of their violation. It is determined that the purpose of this article is an analyse the legal positions of the ECHR and the SC on the legal regulation of liability for breach of insurance obligations in Ukraine. The relevance of the review of these legal positions is due to the adaptation of Ukrainian legislation to international and regional standards of the European Union (EU), and, of course, the need to improve civil liability for breach of insurance obligations. In this study, the author analyses certain judgments of the ECHR and the Supreme Court with a view to determining whether they can be applied in the area of insurance obligations. It is substantiated that ECHR judgments are an international instrument for protecting the rights of individuals in case of breach of insurance obligations, and therefore their application in the course of court proceedings in this category of cases is an effective means of exercising the rights and interests of individuals. The expediency of applying the legal position of the ECHR on the need to observe the "balance of probabilities" in civil proceedings in cases concerning liability for breach of insurance obligations is substantiated, as this is directly dependent on a detailed study of all the circumstances of the case and the proper and impartial application of the norms of substantive law. It is established that the legal positions developed by the ECHR and the Supreme Court in the aspect under study provide a clear understanding of the content of liability for breach of insurance obligations, in particular, arising from road accidents. It is proved that the study indicates the need for further research on the systematisation of the legal positions of the ECHR and the case law of the Supreme Court on the issues of breach of insurance obligations, which will serve as a guide in resolving single-subject cases.